HUBUNGAN MEKANISME KOPING DENGANKEJADIAN STRES DALAM MENGHADAPI WABAH PENYAKIT COVID-19 DI DESA GAMALAMA KOTA TERNATE - Djumati, nurlela (Journal Of Community & Emergency, 2024)
Coping mechanism is a method used by individuals in solving problems, overcoming changes that occur, and threatening situations, both cognitively and behaviorally. Stress is a condition resulting from enviromental changes that are accepted as something that opposes, threatens or damages a person’s equilibrium balance. This study aims to determine the relationship between coping mechanisms and the incidence of stress in dealing with the Covid-19 disease outbreak in Gamalama village, Ternate City. The method or type of research in this study is descriptive analytic research with a Cross Sectional Study approach in which data collection is carried out simultaneously at the same time. This research was carried out in Gamalama village, Ternate City in August - October 2021. The sample in this study amounted to 60 respondents. The variable of this research is the coping mechanism with the occurrence of stress in the face of the covid-19 disease outbreak in Gamalama village, Ternate City. The results of this study indicate that most of the respondents’ coping mechanisms are still in the maladaptive category by 56.7% and most of the respondents experience moderate stress, which is 41.7%. The results of the analysis using the Chi-Square test obtained a significant value of 0.003 or smaller than the alpha value of 0.05 which means there is a significant relationship between coping mechanisms and stress events in dealing with the Covid-19 disease outbreak in Gamalama village, Ternate City. It is recommended to the people of the city of Ternate, especially in the village of Gamalama to always maintain health and always follow health protocols and maintain healthy, halal and good food patterns and maintain cleanliness, carry out positive activities such as exercising regularly.